Model empiris penggunaan e-money di Indonesia - Mustika, Dhia Mega Ayu; Hakim, Abdul (Jurnal Kebijakan Ekonomi dan Keuangan, 2024)
Purpose – This paper analyzes the determinants of e-money usage in Indonesia. The determinants of e-money usage considered are inflation, interest rates from Bank Indonesia (BI-rate), and gross domestic product (GDP). Methods – This paper estimates time series data from 2010 to 2022 in a conditional error correction model with the help of the Eviews 10 software package. Findings – Data analysis found that all independent variables have an effect on e-money, both in the short term and in the long term. Implication – The development of e-money, which has the potential to increase the amount of money in circulation and thus increase inflation, can be controlled by inflation, interest rates, and GDP. Originality – The originality of this paper lies in the use of the conditional ECM model for modeling e-money in Indonesia. Abstrak Tujuan – Paper in menganalisis faktor-faktor penentu penggunaan E-money di Indonesia. Variabel-variabel penentu penggunaan e-money yang dipertimbangkan adalah Inflasi, tingkat bunga dari Bank Indonesia (BI-rate), dan produk domestik bruto (PDB). Metode – Paper ini menggunakan data time series dari tahun 2010 hingga 2022. Paper ini menggunakan model conditional error correction model dengan bantuan program Eviews 10. Temuan –Analisis data menemukan bahwa semua variabel independen berpengaruh terhadap e-money, baik dalam jangka pendek maupun dalam jangka panjang. Implikasi – Perkembangan e-money, yang berpotensi menambah jumlah uang beredar dan dengan demikian bisa meningkatkan inflasi, bisa dikontrol dengan inflasi, tingkat bunga, serta PDB. Orisinalitas – Orisinalitas dari paper ini terletak pada penggunaan model conditional ECM atas pemodelan e-money di Indonesia.